Discovery, Biosynthesis and Stress-Related Accumulation of Dolabradiene-Derived Defenses in Maize. Issue 4 (23rd February 2018) - Mafu, Sibongile; Ding, Yezhang; Murphy, Katherine M.; Yaacoobi, Omar; Addison, J. Bennett; Wang, Qiang; Shen, Zhouxin; Briggs, Steven P.; Bohlmann, Jörg; Castro-Falcon, Gabriel; Hughes, Chambers C.; Betsiashvili, Mariam; et al.
Abstract : This study describes a class of stress-related diterpenoids, termed dolabralexins, in maize and identifies diterpene synthases and a cytochrome P450 involved in their biosynthesis. Abstract: Terpenoids are a major component of maize ( Zea mays ) chemical defenses that mediate responses to herbivores, pathogens, and other environmental challenges. Here, we describe the biosynthesis and elicited production of a class of maize diterpenoids, named dolabralexins. Dolabralexin biosynthesis involves the sequential activity of two diterpene synthases, ENT -COPALYL DIPHOSPHATE SYNTHASE (ZmAN2) and KAURENE SYNTHASE-LIKE4 (ZmKSL4). Together, ZmAN2 and ZmKSL4 form the diterpene hydrocarbon dolabradiene. In addition, we biochemically characterized a cytochrome P450 monooxygenase, ZmCYP71Z16, which catalyzes the oxygenation of dolabradiene to yield the epoxides 15, 16-epoxydolabrene (epoxydolabrene) and 3β-hydroxy-15, 16-epoxydolabrene (epoxydolabranol). The absence of dolabradiene and epoxydolabranol in Zman2 mutants under elicited conditions confirmed the in vivo biosynthetic requirement of ZmAN2. Combined mass spectrometry and NMR experiments demonstrated that much of the epoxydolabranol is further converted into 3β, 15, 16-trihydroxydolabrene (trihydroxydolabrene). Metabolite profiling of field-grown maize root tissues indicated that dolabralexin biosynthesis is widespread across common maize cultivars, with trihydroxydolabrene as the predominant diterpenoid. Oxidative stress induced dolabralexin accumulation and transcript expression of ZmAN2 and ZmKSL4 in root tissues, and metabolite and transcript accumulation were up-regulated in response to elicitation with the fungal pathogens Fusarium verticillioides and Fusarium graminearum . Consistently, epoxydolabranol significantly inhibited the growth of both pathogens in vitro at 10 µg mL −1, while trihydroxydolabrene-mediated inhibition was specific to F . verticillioides . These findings suggest that dolabralexins have defense-related roles in maize stress interactions and expand the known chemical space of diterpenoid defenses as genetic targets for understanding and ultimately improving maize resilience.